Aptitude to machine milking of Merino Beira Baixa ewes. 2. Productive behavior face to hand milking and machine milking - Carreiro, F.M. (2011)
In four groups of ewes, 4 series of measurements to characterize the morphology of the udder were performed, as well as, their milk production every 3 weeks from the beginning of milking (57±7 days after lambing). To each group of 8 animals that included ewes of the lst., 2nd, 3rd and 4th lactation, were distributed the following treatments: group 1-handmilking; group 2-handmilking with ‘repasse’; group 3-machine milking; group 4-machine milking with ‘repasse’. We observed relevant differences in milk production (P<0.05) between handmilking and machine milking. In the groups were “repasse” was done, the milk production was rather superior to the other groups (P<0.05). The average milk production of four measurements (=64) was of: handmilking (group 1+ group 2) = 309,9±138.7 ml; machine milking (group 3 + group 4) = 361.9±130.3 ml; milking without “repasse” (group 1 + group 3) = 289.2±122.1 ml; milking with ‘repasse’ (group 2 + group 4) = 382.6±146.8 ml. In handmilking the parameters that showed higher correlations with milking production were the volume of the udder (r=0.66), the width between the teats (r=0.52) and the depth of the udder (r=0.44). The results obtained with machine milking were: udder width (r=0.49), length of teats (r=0.42), udder volume (r=0.040) and teats inclination (r=0.29).